The rule of the Templars: the French text of the Rule of the Order of the Knights Templar - Upton-Ward, Judith Mary; Curzon, Henri de (Studies in the history of medieval religion, 1992)
von H. de Curzon nach alten Ms. 1886 veröffentlicht